2017
DOI: 10.1007/s11005-017-0993-4
|View full text |Cite
|
Sign up to set email alerts
|

The trace on projective representations of quantum groups

Abstract: Abstract. For certain roots of unity, we consider the categories of weight modules over three quantum groups: small, un-restricted and unrolled. The first main theorem of this paper is to show that there is a modified trace on the projective modules of the first two categories. The second main theorem is to show that category over the unrolled quantum group is ribbon. Partial results related to these theorems were known previously.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…So (4) implies (1). In the proof of Lemma 3 of [18] it is shown that (1) implies (2) and (2) implies (3). To see (3) implies (4): Let ξ ±ra be the eigenvalues of (−1) +1 ψ(χ).…”
Section: A Biquandle Representation From Cyclic Quantum Sl(2) Modulesmentioning
confidence: 98%
See 3 more Smart Citations
“…So (4) implies (1). In the proof of Lemma 3 of [18] it is shown that (1) implies (2) and (2) implies (3). To see (3) implies (4): Let ξ ±ra be the eigenvalues of (−1) +1 ψ(χ).…”
Section: A Biquandle Representation From Cyclic Quantum Sl(2) Modulesmentioning
confidence: 98%
“…This trace restricts to a trace t on the ideal of projective modules Proof. In [17], the use of a Markov trace on the colored braid group was used because at that time the existence of a modified right trace was only known (from [18] we have a modified left and right trace). The above construction is more general because colored braids are Q-tangles and if σ is such a braid whose braid closure is a Q-link L then F (L) = t( F (σ)) by the properties of a modified trace.…”
Section: 5mentioning
confidence: 99%
See 2 more Smart Citations
“…Unrolled quantum groups are certain Hopf algebras that are important in quantum topology [GPT09][CGP15] [GP16]. They are used to construct topological invariants from non-semisimple tensor categories, here the representation category of versions of quantum groups at an even root of unity.…”
Section: Introductionmentioning
confidence: 99%